Organizational citizenship behavior: A study on relationship between leadership styles and organizational citizenship behavior at Naza Automative Manufacturing Sdn. Bhd. Gurun, Kedah / Azlinda Abd Rahim and Ros Syazwani Ahmad - Abd Rahim, Azlinda; Ahmad, Ros Syazwani (2010)
Basically, any organization has their own objective in order to achieve their goal. This paper reviews the leadership styles that are preferred by the employees in Naza Automative Manufacturing Sdn Bhd, Gurun, Kedah which contribute to the Organizational Citizenship Behavior (OCB) and to identify the relationship between Organizational Citizenship Behavior (OCB) with three styles of leadership which are transformational leadership, charismatic leadership, and situational leadership. OCB is a willingness to cooperate, assist voluntarily and contribute to the strength of organization loyalty. It refers to the individual contributions in the workplace that go beyond ordinary role requirement and contractually rewarded job achievement. It has been seen that OCB has continuously been an important issue for almost three decades. It has been classified that leadership styles have played an important role in order to influence employees either positively or negatively